-8=3(n+5)

Simple and best practice solution for -8=3(n+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8=3(n+5) equation:


Simplifying
-8 = 3(n + 5)

Reorder the terms:
-8 = 3(5 + n)
-8 = (5 * 3 + n * 3)
-8 = (15 + 3n)

Solving
-8 = 15 + 3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3n' to each side of the equation.
-8 + -3n = 15 + 3n + -3n

Combine like terms: 3n + -3n = 0
-8 + -3n = 15 + 0
-8 + -3n = 15

Add '8' to each side of the equation.
-8 + 8 + -3n = 15 + 8

Combine like terms: -8 + 8 = 0
0 + -3n = 15 + 8
-3n = 15 + 8

Combine like terms: 15 + 8 = 23
-3n = 23

Divide each side by '-3'.
n = -7.666666667

Simplifying
n = -7.666666667

See similar equations:

| 2(v+8)+9=7 | | 9(8a+7b)= | | 6a-13=4a+57 | | 5x+50=2x+20 | | (9x+3)=(7x+12) | | 6+3x=-16 | | 6(v-1)=6 | | x^2-10xy+6y^2-12=0 | | (x+2)(2x^2-3x+5)= | | (3x+10)=62 | | -6.7(4p+6)-1.7(3p-5)= | | 5x+1=6x-(3x-9) | | 5-2m=-19 | | 6-4c=2/3-1 | | =300-40Y | | 6x^2-6x-3=-1 | | (5x+9)=89 | | -7/2(y-6)-1/4y= | | f(x)=x(x-11) | | 2(w+6)-4w= | | 3(6x+1)=8(5x-10) | | 3^x=1/9 | | -92+42= | | 6x^2-4x-2=-1 | | 9x-9=2+2(x+2) | | (2/x-5)-5(x-5) | | sin24=7/x | | cosx+2cos^2x=0 | | Y=12(1.05)y | | 100[0.06(q+10)]= | | 50x+80(10)=60(x+10) | | 5.7x-5=4.7x |

Equations solver categories